Comparative Analysis of Addressing Terms Expressed by Nouns in English and Uzbek (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates the structural, semantic, and sociolinguistic characteristics of addressing terms realized primarily through nouns in English and Uzbek. Using a comparative typological approach, 312 English and 378 Uzbek address nouns were collected from dictionaries, corpora, and natural discourse. The analysis reveals that English relies heavily on proper names, professional titles, and generic relational nouns, whereas Uzbek exhibits a richer system of kinship-based, age-grade, and honorific nouns with productive derivational morphology. Significant differences are observed in the degree of grammaticalization of respect, the obligatory encoding of relative age, and the integration of Islamic honorific elements in Uzbek. The findings support the hypothesis that addressing systems reflect cultural values of individualism (English) versus hierarchical collectivism and relational identity (Uzbek).